EFEKTIFITAS PPT INTERAKTIF UNTUK PEMBELAJARAN ANAK - ANAK PAUD - I Dewa Ayu Devi Maharani Santika; Ni Wayan Suryani (LOKATARA SARASWATI, 2024)
In the world of education, especially at the Early Childhood Education (PAUD) level, effective learning methods are the main key in forming the foundation of children's education. In the midst of technological advances, the integration of visual aids such as slide shows is increasingly relevant in supporting the learning process. This service activity aims to optimize the use of slide shows to improve the quality of learning at PAUD Hooray School. Activities include several activity specifications, namely developing interactive slide shows, creating interesting and informative slide material, training teachers in using slide shows, and carrying out evaluations of the effectiveness of using slide shows. The hope to be achieved through this activity is to create a more dynamic and interactive learning environment through the use of slide shows designed taking into account children's cognitive, motoric and social development. Although faced with challenges such as adapting visual materials to suit the child's age, this activity shows great potential in increasing student engagement and understanding during the learning process. Assistance in making interactive PPTs can help teachers carry out teaching activities more optimally.